Mentoring Function and Quality of Supervisor Auditor Relationship: Organizational Justice as A Mediation - Rahmawati Rahmawati; Rispantyo Rispantyo; Subekti Djamaluddin (Universitas Pasundan, 2017)
This study empirically examines the antecedents and consequences of organization justice consisting of distributive justice, procedural justice, and interactional justice. The hypothesis of this study are mentoring function positive effect on organization justice, organizational justice positive effect on quality of supervisor-auditor relationship, mentoring function positive effect on quality of supervisor-auditor relationship. In additional, this study also hypothesized that organization justice as mediation between mentoring functions and quality of supervisor-auditor relationship. This study is a survey of 228 government internal auditors of Financial and Development Supervisory Agency-Badan Pengawasan Keuangan dan Pembangunan (BPKP) in Java-Bali Indonesia. The technique of collecting data using questionnaires. Test hypotheses using path analysis with SEM-AMOS. The results showed that mentoring function positive effect on organization justice, organizational justice positive effect on quality of supervisor-auditor relationship, mentoring function positive effect on quality of supervisor-auditor relationship. The study also provide an empirical finding that organization justice as mediation between mentoring functions and quality of supervisor-auditor relationship. The study provides recommendations to the BPKP in solving the problems faced by the government in realizing good and clean governance. This study is the first empirically examines the potential benefit of organization justice as a mediation between mentoring function and quality of supervisor-auditor relationship.